Justification of Choice of Heating System for Pigsty - Boltіanska, Natalia; Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна (My University, 2018)
The article analyzes the types of heating systems for heating the pig farm. The specific weight of heat supply processes and microclimate provision in the total expenditures of fuel and energy resources in the premises for keeping pigs is given. The necessary temperature regime for sows, piglets weeks from birth and pigs for fattening was determined. The factors that have a significant influence on the selection of the system of heating and ventilation of the pig farm are determined. The shortcomings and advantages of systems using open energy sources when burning gas or other fuels and systems using a water heat carrier are given. The advantages and disadvantages of infra-red heating, fan convectors, "dark radiators", "aquasolar", "warm" floor, heating of pigsties with a solid concrete floor with plastic or metal pipes laid in it, along which the coolant circulates, are analyzed. Equipment for water heating in premises with weaned piglets is considered: delta pipes, twin tubes, butterfly pipes - with two, three or four plates.
Keywords: pigsty; microclimate; heat supply; heating system; ventilation system; advantages and disadvantages; infrared heating; coolant